If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2(8 + -1x) = -16 3x + (8 * -2 + -1x * -2) = -16 3x + (-16 + 2x) = -16 Reorder the terms: -16 + 3x + 2x = -16 Combine like terms: 3x + 2x = 5x -16 + 5x = -16 Add '16' to each side of the equation. -16 + 16 + 5x = -16 + 16 Combine like terms: -16 + 16 = 0 0 + 5x = -16 + 16 5x = -16 + 16 Combine like terms: -16 + 16 = 0 5x = 0 Solving 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '5'. x = 0 Simplifying x = 0
| 5x(-3x)=-15x^2 | | 7.20x+5.50y=52.75 | | k/21=14/49 | | 3+6x=5x | | 2b-3=6 | | 13c^5d^5-169cx^4d^3=0 | | 10/16=15/p | | Y=150+10 | | 71/4×1/18 | | C-12=2 | | 4/5=m/35 | | 8+a=7 | | 15(6x-8)=14(x-5)-2 | | x-9-51=918 | | 2a-4=5 | | 6*11y/2 | | 8d=4 | | -16t^2+126t=126+5 | | -16t^2+126t=136+5 | | y=150+-20x | | 7dy+3xy-3xv-7dv=0 | | x+11-19=228 | | (1/3x^8)(1/7x^5) | | 6(11y/2) | | 3y+4=7y-4 | | 25=5x-16 | | 35x^27+24x^19-15x^13= | | y/8-y/6 | | y=-200+150 | | 6y=14+4x | | 100+2x=6x | | 6lx^3+x^2-1=0 |